Sister Carrie - Dreiser, Theodore, 1871-1945 (Barnes & Noble Classics, 2005)
When small-town Carrie arrives in 1890s Chicago, she cannot know what awaits. Callow beautiful, and alone, she experiences the bitterness of temptation and hardship even as she sets her sights on a better life.